Development of a Chinese College Students' Attitudes Toward Sexual Swear Words Scale - Wei, Ying; Chen, Qingsong (Frontiers in Psychology, 2021)
Sexual swear words are frequently used and considered vulgar and controversial in Chinese. The study of attitude is not only an important part of the study of swear words, but is also an important way for predicting their use. To date, few independent studies have been conducted on Chinese sexual swear words; those that have been conducted mostly focus on language ontology rather than language use. The studies have mainly used qualitative research methods, with a lack of empirical analysis and use of measurement tools. It is feasible and necessary to study college students as the object of sexual swear words because of the prevalence of “Zu'an culture” and the abuse of sexual swear words. Based on the current research status of Chinese swear words and the context of using swear words on campus, this paper combines the research of linguistic differences in swearing, psychological theories, and social science measurement theories and uses SPSS and Mplus statistical software to develop Chinese college students' attitudes toward Sexual Swear Words Scale. The participants consist of students from Zhejiang Normal University and other universities. A total of 262 college students participated in the preliminary test. Through item analysis and exploratory factor analysis, the formal scale was formed. A total of 608 college students were formally tested, and confirmatory factor analysis, reliability, and validity tests were carried out to produce the final scale. The scale contains three subscales: Cognition (17 items), Affection (17 items), and Behavior Tendency (15 items). The results show that each subscale model fits well, has good reliability and validity, and can be used as an important tool to measure attitudes of Chinese college students toward sexual swear words.